Panorama of the sustainable development civilization - Skowroński, Antoni (Studia Ecologiae et Bioethicae, 2020)
The article is about the conception of sustainable development settled in the context of cultural and civilization changes. It can be taken as an alternative to further civilization development and a new panorama, opening up perspectives for the further sustainable development of civilization. The conception is a global strategy of development. It relies on the including of the natural environment into the social and economic development of a region, country or, from a global perspective, of the whole world. It assumes a long-lasting improvement of the quality of life of the present and future generations which is integrally associated with environmental improvement. It also shows the necessity of the spiritual growth and changes of the material aims of the development into immaterial ones. In all these aims and assumptions, there are a lot of practical and mental problems in the sphere of sustainable development which retard and even make it impossible to put these conceptions effectively into life.